2020
DOI: 10.1002/iub.2273
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐34a‐mediated death of acute myeloid leukemia stem cells through apoptosis induction and exosome shedding inhibition via histone deacetylase 2 targeting

Abstract: We investigated the role of leukemia stem cells in chemoresistance and recurrence of acute myeloid leukemia. Total RNA was isolated from cells or tissues using TRIzol reagent. Cell viability was assessed with the tetrazolium assay. MicroRNA‐34a (miR‐34a), which acts on cell death regulation pathways, was noticeably downregulated in non‐M3 acute myeloid leukemia stem cells compared with normal hematopoietic stem cells. Furthermore, inhibition of miR‐34a‐mediated suppression in leukemia stem cells was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Therefore, finding strategies to specifically eliminate LSCs may be necessary for solving AML recurrence or drug resistance ( Peng et al, 2018 ). Hu et al (2020) found that miR-34a was elevated in exosomes derived from LSCs. miR-34a could impede the secretion of exosomes which was promoted by RAB27B through inhibiting the expression of RAB27B.…”
Section: Role Of Exosomal Mirnas In Leukemiamentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, finding strategies to specifically eliminate LSCs may be necessary for solving AML recurrence or drug resistance ( Peng et al, 2018 ). Hu et al (2020) found that miR-34a was elevated in exosomes derived from LSCs. miR-34a could impede the secretion of exosomes which was promoted by RAB27B through inhibiting the expression of RAB27B.…”
Section: Role Of Exosomal Mirnas In Leukemiamentioning
confidence: 98%
“…This process could increase the miR-34a level of LSCs in which miR-34a could inhibit HDAC2 expression and regulated the JAK1/STAT2/p53 pathway to promote the clearance of LSCs. However, LSCs took away the tumor-suppressive miR-34a by secreting exosomes, leading to the decrease of miR-34a in LSCs and the abnormal proliferation of LSCs ( Hu et al, 2020 ). Similarly, miR-34c-5p has also been observed to promote LSCs clearance whereas RAB27B-mediated extracellular transfer of miR-34c-5p through exosomes partly promoted the miR-34c-5p decrease in LSCs, thus promoting the growth of LSCs ( Peng et al, 2018 ).…”
Section: Role Of Exosomal Mirnas In Leukemiamentioning
confidence: 99%
“…In non‐M3 acute myeloid leukemia stem cells, MicroRNA‐34a (miR‐34a) is significantly downregulated compared with normal hematopoietic stem cells. However, miR‐34a induces apoptosis by targeting histone deacetylase 2, and the inhibition of exosome shedding mediates stem cell death in acute myeloid leukemia 57 . Exosomes produced by cancer cells are known to regulate lung cancer development by promoting epithelial‐mesenchymal transition of tumor cells, inducing angiogenesis, establishing a premetastatic microenvironment, and evading the immune system 58 .…”
Section: Exosomes In Different Types Of Pcdmentioning
confidence: 99%
“…Apparently, miR‐181a or a specific EV has a role in central nervous system involvement in Pediatric Acute Lymphoblastic Leukemia (PALL) and miR‐181a inhibitor may show hopeful results in PALL treatment 137 . miR‐34a is highly efficient in the treatment of AML patients via inhibiting exosome releasing and inducing cell death by increasing the expression of the Janus Kinase 1/Signal Transducer and Activator of Transcription protein‐2 (JAK1/STAT2)/p53 pathway 138 . Regarding the role of exosomal miR‐222‐3p derived from BM‐MSCs in inducing apoptosis by interferon regulatory factor 2 signaling pathway and inhibiting cell proliferation, they can be a novel therapeutic approach in myeloid leukemia 139 .…”
Section: Exosomes Effect On Leukemia Treatmentmentioning
confidence: 99%
“…137 miR-34a is highly efficient in the treatment of AML patients via inhibiting exosome releasing and inducing cell death by increasing the expression of the Janus Kinase 1/Signal Transducer and Activator of Transcription protein-2 (JAK1/STAT2)/p53 pathway. 138 Regarding the role of exosomal miR-222-3p derived from BM-MSCs in inducing apoptosis by interferon regulatory factor 2 signaling pathway and inhibiting cell proliferation, they can be a novel therapeutic approach in myeloid leukemia. 139 Interestingly, a prior study focusing on serum exosomal miRNA-125b in AML patients identified an up-regulation of this miRNA to be strongly associated with elevation of relapse and risk of mortality.…”
Section: Exosomes Effect On Leukemia Treatmentmentioning
confidence: 99%